Transmission characteristics and inactivated vaccine effectiveness against transmission of the SARS-CoV-2 Omicron BA.2 variant in Shenzhen, China - He, Xiaofeng; Liao, Yuxue; Liang, Yuanhao; Yu, Jiexin; Gao, Wei; Wan, Jia; Liao, Yi; Su, Jiao; Zou, Xuan; Tang, Shixing (Frontiers in Immunology, 2024)
We conducted a retrospective cohort study to evaluate the transmission risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron BA.2 variant and the effectiveness of inactivated COVID-19 vaccine boosters in Shenzhen during an BA.2 outbreak period from February 1 to April 21, 2022. A total of 1,248 individuals were infected with the BA.2 variant and 7,855 close contacts were carefully investigated. The risk factors for high secondary attack rate of SARS-CoV-2 infection were household contacts (adjusted odds ratio [aOR]: 1.748, 95% confidence interval [CI]: 1.448, 2.110), younger individuals aged 0-17 years (aOR: 2.730, 95% CI: 2.118, 3.518), older persons aged ≥ 60 years (aOR: 1.342, 95% CI: 1.135, 1.588), females (aOR: 1.442, 95% CI: 1.210, 1.718), and the subjects exposed to the post-onset index cases (aOR: 8.546, 95% CI: 6.610, 11.050), respectively. Compared to the unvaccinated and partially vaccinated individuals, relatively low risk of secondary attack was found for the individuals who received booster vaccination (aOR: 0.871, 95% CI: 0.761, 0.997). Moreover, high transmission risk was found for the index cases aged ≥ 60 years (aOR: 1.359; 95% CI: 1.132, 1.632) while relatively low transmission risk was observed for the index cases who received full vaccination (aOR: 0.642, 95% CI: 0.490, 0.841) and booster vaccination (aOR: 0.676, 95% CI: 0.594, 0.770). Compared with full vaccination, booster vaccination of inactivated COVID-19 vaccine showed an effectiveness of 24.0% (95% CI: 7.0%, 37.9%) against BA.2 transmission for the adults ≥ 18 years and 93.7% (95% CI: 72.4%, 98.6%) for the adults ≥ 60 year whereas the effectiveness was 51.0% (95% CI: 21.9%, 69.3%) for the individuals of 14 to 179 days after booster vaccination and 51.2% (95% CI: 37.5%, 61.9%) for the non-household contacts. The estimated mean values of the generation interval, serial interval, incubation period, latent period, and viral shedding period were 2.7 days, 3.2 days, 2.4 days, 2.1 days, and 17.9 days, respectively. In summary, our results confirmed that the main transmission route of Omicron BAsubvariant was household contact, and booster vaccination of the inactivated vaccines was relatively effective against BA.2 subvariant transmission in older people.